Deductive Systems in Traditional and Modern Logic - Wybraniec-Skardowska, Urszula; Citkin, Alex (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The book provides a contemporary view on different aspects of the deductive systems in various types of logics including term logics, propositional logics, logics of refutation, non-Fregean logics, higher order logics and arithmetic.